2014
DOI: 10.1128/iai.01357-13
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ferric Reductases in Iron Acquisition and Virulence in the Fungal Pathogen Cryptococcus neoformans

Abstract: Iron acquisition is critical for the ability of the pathogenic yeast Cryptococcus neoformans to cause disease in vertebrate hosts. In particular, iron overload exacerbates cryptococcal disease in an animal model, defects in iron acquisition attenuate virulence, and iron availability influences the expression of major virulence factors. C. neoformans acquires iron by multiple mechanisms, including a ferroxidase-permease high-affinity system, siderophore uptake, and utilization of both heme and transferrin. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 59 publications
(117 reference statements)
1
77
1
Order By: Relevance
“…We previously demonstrated that defects in the components of the haem uptake system (i.e. Cig1, Rim101 and Vps23) cause reduced susceptibility to MPs (Cadieux et al ., ; Hu et al ., ; Saikia et al ., ). We therefore predicted that the ESCRT‐II and ‐III complexes would also influence susceptibility to MPs if they participated in haem uptake.…”
Section: Resultsmentioning
confidence: 98%
“…We previously demonstrated that defects in the components of the haem uptake system (i.e. Cig1, Rim101 and Vps23) cause reduced susceptibility to MPs (Cadieux et al ., ; Hu et al ., ; Saikia et al ., ). We therefore predicted that the ESCRT‐II and ‐III complexes would also influence susceptibility to MPs if they participated in haem uptake.…”
Section: Resultsmentioning
confidence: 98%
“…Previously, we showed that heme or a siderophore can restore growth on fluconazole for the C . neoformans cfo1 and cft1 mutants defective in high‐affinity iron uptake (Hu et al, ; Jung et al, ; Kim et al, ; Saikia, Oliveira, Hu, & Kronstad, ). This may be due to upregulation of uptake functions in the mutants due to iron starvation or to direct rescue of heme‐containing enzymes for ergosterol biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, FRE2 is required for robust growth in the presence of heme and transferrin, and for full virulence in a mouse inhalation model of cryptococcosis. 29 Similar to the S. cerevisiae FRE genes, the FRE genes in both C. albicans and C. neoformans also show differential transcriptional regulation in the presence of copper. 29,30 …”
Section: Reductive Iron Uptake: Connections With Virulence and Dimmentioning
confidence: 93%
“…In C. neoformans , eight genes encoding putative ferric reductases have been identified ( FRE1–7 , FRE201 ). 29 Notably, the transcription of FRE2 and FRE4 is regulated by hemin or FeCl 3 suggesting a crucial role of these genes in maintaining iron homeostasis during iron-limited conditions. Furthermore, FRE2 is required for robust growth in the presence of heme and transferrin, and for full virulence in a mouse inhalation model of cryptococcosis.…”
Section: Reductive Iron Uptake: Connections With Virulence and Dimmentioning
confidence: 99%